Potential role of acetylsalicilic acid and other non-steroidal anti-inflammatory drugs in cancer risk reduction (literature review) - Buheruk, V. V.; Voloshyna, O. B.; Kovalchuk, L. I.; Balashova, I. V.; Naidionova, O. V. (Zaporozhye Medical Journal, 2021)
The aim of this review is to analyze and summarize the existing evidence regarding the possibilities of using acetylsalicylic acid (ASA) and other non-steroidal anti-inflammatory drugs (NSAIDs) to reduce cancer risk. Conclusions. Chronic inflammation facilitates the onset and progress of tumour growth. Anti-cancer properties of acetylsalicylic acid and other non-steroidal anti-inflammatory drugs are mediated via cyclooxygenase COX-dependent mechanisms, as well as other tumorigenic pathways. Current systematic review addresses potential role of ASA and other NSAIDs in reduction of cancer risk for the following localizations: head and neck, lungs, gastrointestinal tract, breast, ovaries, prostate, and skin. The role of ASA in primary prevention of colorectal cancer in specific populations is presented in 2016 U. S. Preventive Services Task Force guidelines. Studies indicate heterogeneous protective potential of ASA against different cancer types, depending on studied population, duration of intake and dose. Influence of non-aspirin NSAIDs on cancer morbidity and mortality is more controversial.